Review of the Process of Producing the Motion of the Youth MPs Conference through Creative Thinking Skills - Nasrul Hakim Salleh; Marwan Ismail (Journal of Social Transformation and Regional Development, 2021)
Creative thinking skills are the main foundation that needs to be applied among Youth MPs. These thinking skills will help APBM formulate the proposals for debate before being appointed as a youth development policy. In accordance with PBM which serves as a medium for youth leaders to get involved in the process of forming youth development policy. This study uses an in-depth interview method involving 9 informants representing 9 PBM Committees. APBM’s creative thinking skills process consists of nine themes namely; knowledge, understanding issues, framework building, information gathering, spirituality, information enlightenment, understanding/clarity of issues, production of proposals, and review of motions. As a result, APBM is able to formulate proposals to be debated in the PBM conference.